4
$\begingroup$

What is the function $f$ who's Taylor series is $1 - \frac{x}{4} + \frac{x^2}{7} - \frac{x^3}{10} + \cdots$ ?

I need to find the value of the series $ \sum^{\infty}_{n = 0}a_n = 1 - \frac{1}{4} + \frac{1}{7} - \frac{1}{10} + \cdots$ by finding $\lim_{x\rightarrow1^-} \sum^{\infty}_{n = 0}a_n x^n$. (Abel Summability)

I already did this for another problem. I was given the series $\sum^{\infty}_{n = 0}b_n = \frac{1}{2\cdot 1} - \frac{1}{3\cdot 2} + \frac{1}{4\cdot 3} - \frac{1}{5\cdot 4} + \cdots$

I showed that $\sum^{\infty}_{n = 0}b_n x^n = \frac{\ln(1+x)}{x^2}+\frac{\ln(1+x)}{x}-\frac{1}{x}\rightarrow 2\ln(2)-1$ as $x\rightarrow1^- \Rightarrow \sum^{\infty}_{n = 0}b_n = 2\ln(2)-1$. (This checks out numerically, as well)

However, I'm having trouble finding the functional representation of $ \sum^{\infty}_{n = 0}a_n x^n$

$\endgroup$
  • 2
    $\begingroup$ A closed form by hypergeometric function is given by wolframalpha. I think you can give up on this approach. $\endgroup$ – Henricus V. Feb 24 '16 at 2:26
14
$\begingroup$

Write the series as

$$\sum_{k=0}^{\infty} \frac{(-1)^k x^k}{3 k+1} = \sum_{k=0}^{\infty} \frac{(-1)^k \left (x^{1/3} \right )^{3 k}}{3 k+1} = x^{-1/3} \sum_{k=0}^{\infty} \frac{(-1)^k \left (x^{1/3} \right )^{3 k+1}}{3 k+1}$$

Consider

$$f(y) = \sum_{k=0}^{\infty} \frac{(-1)^k y^{3 k+1}}{3 k+1}$$ $$\implies f'(y) = \sum_{k=0}^{\infty} (-1)^k y^{3 k} = \frac1{1+y^3} $$ $$\implies f(y) = \int \frac{dy}{1+y^3} = -\frac{1}{6} \log \left(y^2-y+1\right)+\frac{1}{3} \log (y+1)+\frac{\arctan{\left(\frac{2 y-1}{\sqrt{3}}\right)}}{\sqrt{3}} +C$$ $$f(0)=0 \implies C=\frac{\pi}{6 \sqrt{3}} $$ The above integral is evaluated using a partial fraction decomposition. Thus, the original sum is equal to

$$\sum_{k=0}^{\infty} \frac{(-1)^k x^k}{3 k+1} = \frac{\pi x^{-1/3}}{6 \sqrt{3}} + \frac{x^{-1/3}}{6} \log{\left [\frac{\left (1+x^{1/3}\right )^2}{1-x^{1/3}+x^{2/3}} \right ] } + \frac{x^{-1/3}}{\sqrt{3}} \arctan{\left(\frac{2 x^{1/3}-1}{\sqrt{3}}\right)}$$

The limit as $x \to 1^-$ of this sum is then equal to

$$\frac{\pi}{3 \sqrt{3}} + \frac13 \log{2} $$

$\endgroup$
2
$\begingroup$

If $f(x) =\sum_{k=0}^{\infty} a_k x^k $, then $f_{n, j}(x) =\sum_{k=0}^{\infty} a_{j+kn} x^{j+kn} =\frac1{n}\sum_{i=0}^{n-1} w^{ij} f(w^i x) $ where $w = e^{2\pi i /n} $.

This is known as multisection of series. Here is one of many available discussions:

http://mathworld.wolfram.com/SeriesMultisection.html

Since $f(x) =\frac{-\ln(1-x)}{x} =\sum_{k=0}^{\infty} \frac{x^k}{k+1} $, $\sum_{k=0}^{\infty} \frac{x^{3k}}{3k+1} =f_{0, 3}(x) =\frac1{3}\sum_{i=0}^{2} f(w^i x) $ where $w = e^{2\pi i /3} $.

Since you want $g(x) =\sum_{k=0}^{\infty} \frac{(-1)^kx^k}{3k+1} $, $g(x) =f_{0, 3}((-x)^{1/3}) $.

$\endgroup$
1
$\begingroup$

We can get a closed form with elementary functions.

Let f(x) be the function. Define u=x^(1/3) and then g(u) = u*f(u^3). Then g'(u) is a geometric series summing to 1/(1+u^3). With g(0)=0 we can now set up g(u) as a definite integral. This is carried out via partial fractions giving logarithmic and inverse tangent terms (plus a constant, as the inverse tangent term is not zero at the lower limit of the integral). Divide that result by u and then put in u=x^(1/3) to get f(x). The result is rather complicated as a function of x, but simplifies considerably for x=1.

If I have this right, the numerical result should be 0.8356... .

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.